Protein Kinase C-delta (PKCδ) in Neurodegeneration and Cerebral Ischemia: Molecular Mechanisms and Therapeutic Implications - Yi-Heng Hsieh; I-Yen Lee; You Lien; Lon-Fye Lye; Yen-Chuan Ou; Ding-I Yang (Cell Biochemistry and Biophysics, 2026)
Protein kinase C delta (PKCδ), a calcium-independent novel PKC isoform, is increasingly recognized as a compartmentalized regulator of stress signaling in the central nervous system. Through tyrosine phosphorylation, subcellular translocation, regulation of its expression, and caspase-3-dependent proteolytic activation, PKCδ can convert transient adaptive responses into sustained oxidative, mitochondrial, inflammatory, and nuclear apoptotic signaling. This review evaluates PKCδ across Parkinson’s disease (PD), Alzheimer’s disease (AD), Huntington’s disease (HD), and ischemic stroke, emphasizing disease- and cell type-specific mechanisms rather than a uniformly pathogenic role. In PD, PKCδ most consistently amplifies toxin- and α-synuclein-associated dopaminergic injury and glial inflammation, although human evidence remains limited. In AD, PKCδ may link amyloidogenic processing of amyloid precursor protein (APP), amyloid-beta peptide (Aβ)-induced neuronal stress/cell cycle reentry, and glial neuroinflammation in a context-dependent feed-forward circuit. In HD, PKCδ signaling may shift from early compensatory downregulation to stress-induced apoptotic reactivation. In ischemic stroke, the strongest evidence implicates PKCδ in reperfusion-associated oxidative and inflammatory injury, particularly through neutrophil and translocation-dependent mechanisms. Future therapeutic development will require isoform-selective, compartment-specific, and cell type-resolved PKCδ modulation.

Comparative Efficacy of Coriander Seed Extract-Loaded Selenium Nanoparticles and DMSA in Restoring Antioxidant/Apoptotic Balance of Lead-Induced Hepatotoxicity - Eslam Elshaier; Abdel Ghany F. Shoair; Rehab Reda Hassan; Mansour Emad; Noureen ELKattan; Ahmed Khalifa; Mohamed Essam; M. M. Farag; Fayez Althobaiti; Marwa M. M. Fawzy; Heba A. Sahyon (Cell Biochemistry and Biophysics, 2026)

Elucidation of Baicalein’s Anti-Intervertebral Disc Degeneration Mechanism Through Network Pharmacology and Experimental Validation - Rui Wang; Zhiyong Liu; Xiaopeng Zhao (Cell Biochemistry and Biophysics, 2026)
This study aims to elucidate the biological effects of Baicalein (BA) on intervertebral disc degeneration (IDD) and the potential mechanisms involved. Network pharmacology analysis was performed to identify the core targets and signaling pathways responsible for the therapeutic effects of BA on IDD. In vitro validation was carried out using IL-1β-stimulated nucleus pulposus cells (NPCs). Cell viability, apoptosis, inflammatory cytokines (TNF-α, IL-6), extracellular matrix (ECM)-related molecules (MMP3, Aggrecan, Collagen II), and the phosphorylation of ERK and p38 were measured using CCK-8 assay, flow cytometry, qRT-PCR, ELISA and Western blot. Network pharmacology identified 80 common targets and highlighted the MAPK signaling pathway as a key mechanism. In vitro, BA (50 µmol/L) mitigated IL-1β-induced cytotoxicity in NPCs and promoted cell proliferation. BA significantly inhibited apoptosis by regulating the Bcl-2/Bax family and cleaved c-caspase-3. It also decreased the expression of TNF-α and IL-6, and reversed ECM homeostasis by modulating MMP-3, Aggrecan and Collagen II expression. Furthermore, BA treatment effectively suppressed IL-1β-induced phosphorylation of ERK and p38. Notably, the MAPK agonist anisomycin partially abolished the above protective phenotypes of BA and restored MAPK phosphorylation. BA alleviates apoptosis, inflammatory response and ECM degradation in NPCs, to retard IDD development mainly through inhibiting MAPK pathway activation, supporting the clinical translational potential of BA for IDD treatment.

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

ARAP3 Facilitates Glioma Progression via IGF2BP3-Mediated m6A Modification Stabilization - Jinmiao Li; Huiping Yu; Jinning Zhang; Jincong Huang (Cell Biochemistry and Biophysics, 2026)

ABCC6 in Cellular Metabolic Homeostasis: Biochemical Links to Extracellular Nucleotide Signaling, Mitochondrial Stress, and Senescence - Lingjuan Yang; Fangsicheng Zhang; Yilu Duan; Ying Li; Jiayi Tang; Xinyuan Zhao; Xiaoke Wang (Cell Biochemistry and Biophysics, 2026)

In vivo and In Silico Assessment of Acampe papillosa (Lindl.) Lindl. Seed Extract: A Multi-Pharmacological Approach - Nusaiba Nujhat; Jannatul Naima Meem; Shyra Tasmia; Nowsheen Sayra; Md. Arifuzzaman; Kamrul Hassan; Ali Ahsan Md. Mozahid; S. M. Moazzem Hossen (Cell Biochemistry and Biophysics, 2026)

Host-Derived Proteomic Profiling of Human and Canine Mammary Tumor Xenografts Identifies Enrichment of Lipid Metabolism-Related Pathways - Elisa Díaz-Grijuela; Saioa Goñi; Alejandro Urdiciain; Miguel Barajas; Ileana B. Gonzalez-Valdes; Maider Espinal; Claudia Caballero-Mínguez; Enrique Santamaria; Agustín Hernández; Egoitz Astigarraga; Gabriel Barreda-Gómez; Raquel Urtasun; et al. (Cell Biochemistry and Biophysics, 2026)
Breast cancer is the most frequently diagnosed cancer in women worldwide and one of the most common malignancies in dogs. Notable clinical, hormonal and molecular similarities between both species suggest that dogs may serve as a valuable comparative oncology model. Alterations in lipid homeostasis and metabolism are closely associated with the acquisition of cancer hallmarks. In this study, a comparative proteomic analysis of murine host-derived proteins was performed in cell line-derived xenograft (CDX) models generated from human triple-negative breast cancer cell line (MDA-MB-231) and a canine mammary carcinoma cell line (CMT-U27). Using LC-MS/MS and species-resolved proteomics, tumor-associated changes in the host proteome were characterized across models. In total, 577 proteins were differentially identified in tumor tissues compared with healthy mammary gland samples in this interspecies CDX comparison, with 51.99% showing increased and 46.79% decreased relative abundance, while a small proportion displayed opposite regulation patterns between models. Functional enrichment analysis revealed that several biological processes were altered, including pathways related to lipid metabolism. Moreover, proteins involved in lipid pathways showed a moderate level of concordance between models ( r > 0.6, Mann-Whitney U test p

METTL3-Mediated m6A Modification of ACTR2 Promotes Trophoblast Cell Growth, Migration and Invasion in Unexplained Recurrent Spontaneous Abortion - Maohua Ren; Lina Wang; Rongqin Li; Jianrong Liu (Cell Biochemistry and Biophysics, 2026)

Nanobodies Open New Avenues in Cancer Treatment: From Molecular Engineering to Therapeutic Platforms - Glenda Romero-Hernández; Mario S. Valdés-Tresanco; Ernesto Moreno (Cell Biochemistry and Biophysics, 2026)

Gomisin A Attenuates Cerebral Ischemia/Reperfusion Injury Through Activation of the VEGF/PI3K/AKT/NOS3 Signaling Pathway - Chenghe Zhao; Jiayue Yu; Kexin Liu; Shuangling Wang; Wenping Jing; Ziyi Zhao; Wenyue Zhuang (Cell Biochemistry and Biophysics, 2026)

Asparagus Polysaccharide Ameliorates TNF-α-Mediated MH7A Cell Dysfunction and Collagen-Induced Arthritis in Mice - Mingfeng Yang; Fangyan Xu; Bin Zhang; Lijun Xu (Cell Biochemistry and Biophysics, 2026)

A Three-Dimensional Hyaluronic Acid-Based Scaffold Model for Electroporation-Enhanced Resveratrol Therapy in Triple-Negative Breast Cancer - Pragatheiswar Giri; Monica Dettin; Annj Zamuner; Maria Teresa Conconi; Ignacio G. Camarillo; Nicolò Martinelli; Luigi Dall’Olmo; Elisabetta Sieni; Raji Sundararajan (Cell Biochemistry and Biophysics, 2026)
Triple-negative breast cancer (TNBC) is an aggressive malignancy defined by the absence of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). These molecular characteristics render targeted therapies less effective and contribute to poor clinical outcomes. Towards this, we studied the electroporation-mediated delivery of resveratrol, a polyphenolic compound with pleiotropic anticancer activities, on MDA-MB-231, human TNBC cell line. Both conventional two dimensional (2D) monolayer cell culture and three-dimensional (3D) hyaluronic acid HA-EAbuK-IKVAV scaffold-based cell cultures were used. Two electroporation (EP) protocols (EP1: 8 pulses, 800 V/cm, 100 µs at 1 Hz; EP2: 8 pulses, 1000 V/cm, 100 µs at 1 Hz) were evaluated for their effects on cytotoxicity and reactive oxygen species (ROS) generation. In 3D, the combined treatment similarly reduced viability to 20% (EP1 + Resv) and 17% (EP2 + Resv), whereas in 2D, the viability reduction is 24% and 18%, respectively. Mechanistically, ROS levels increased substantially with the combination treatment: in 2D, ROS rose to 3 times (EP1 + Resv) and around 3.5 times (EP2 + Resv) the control, while in 3D, ROS increased to 2.4 times (EP1 + Resv) and 2.9 times (EP2 + Resv). Moreover, the combined treatment of electroporation and resveratrol administration on 3D HA-EAbuK-IKVAV-cultured cells decreased the expression of cell cycle regulatory protein Cdk2 and proliferation marker Ki67. These findings highlight the importance of 3D microenvironmental cues in modulating TNBC responsiveness to resveratrol and underscore the potential of combining electroporation with natural compounds as a rational therapeutic strategy for this challenging subtype of breast cancer.

Mechanistic Insights into Aldose Reductase-Dependent Modulation of Hypoxia-Inducible Factor-1α in Promoting Renal Fibrosis - Wenke Zhao; Haoyu Wang; Jingjing Yan; Lutan Zhou; Wei Xu; Xianwei Li (Cell Biochemistry and Biophysics, 2026)

Long-Term Culture of U87MG Glioblastoma Cells Reprograms Metabolism, Impacts Aggressiveness and Alters Drug Responses - Alina A. Isakova; Nadezhda V. Antipova; Diana V. Mazur; Irina N. Druzhkova; Alena I. Gavrina; Margarita L. Shuvalova; Olga I. Patsap; Dmitry A. Bondarenko; Arkadiy N. Murashev; Mikhail P. Kirpichnikov; Marine E. Gasparian; Anne V. Yagolovich; et al. (Cell Biochemistry and Biophysics, 2026)

Kinetic and Apparent Thermodynamic Analysis of Phaseolus Vulgaris Leucoagglutinin Binding to Cell-Surface Glycans in SR Lymphoma Cells Using a Fixation-Modified Cell-ELISA - Qais M. Abdulhameed; Hassanain K Al-Bairmani; Ahmed Majeed Al-Shammari (Cell Biochemistry and Biophysics, 2026)

Secretome Derived from Umbilical Cord Mesenchymal Stem Cells as a Therapeutic Approach for Osteoarthritis: Insights from In Vitro, In Vivo, and Clinical Evidence - Wahyu Widowati; Lydia Lydia; Gabriella Rumayauw J; Monica Permatasari Wijaya; Megan Caroline S. S; Jose Hady Putera; Merisa Noviliany Rachmad; Rizal Aziz; Rizky Pratama; Elnaz Zand (Cell Biochemistry and Biophysics, 2026)

FOXO1 Promotes Mitophagy in Granulosa Cells by Targeting the METTL3/SMAD4 axis - Lan Luo; Mi Tang; Yanli Peng; Xi Chen; Yaqi Liu; Jialan Cui (Cell Biochemistry and Biophysics, 2026)

Resveratrol Modulates Lung Cancer-Associated Hub Genes Identified by Integrated Bioinformatics, Single-Cell Analysis, Molecular Docking, and Experimental Validation - Jinghua Yang; Hanxiu Wei; Jie Li; Jun Chen (Cell Biochemistry and Biophysics, 2026)

Optogenetic Pacemaker Cells for Biological Cardiac Rhythm Management in Sick Sinus Syndrome - Versha Devi; Syeda Aliza Aamir; Syed Abdullah Shah; Muhammad Dawood Ghaffar; Muhammad Talha; Muneeb Saifullah (Cell Biochemistry and Biophysics, 2026)

Machine Learning-Derived Sarcopenia Signature Identifies High-Risk Molecular State in T2D Skeletal Muscle - Qiyao Zhao; Qiwang He; Sining Wang; Hanzhi Wang; Zheyuan Zhang; Zhi Shang; Yue Dong (Cell Biochemistry and Biophysics, 2026)

Probing Voltage Dependence Interaction of Cationic Peptides with Bacterial Porins at A Single-Molecule Level - Sonal Prasad (Cell Biochemistry and Biophysics, 2026)
This study examined how cationic α‑helical antimicrobial peptides such as protamine exchange between the aqueous phase and the transmembrane β‑barrel porin OmpF ( E. coli ) at the single‑molecule level. High‑resolution conductance recordings in planar lipid bilayers revealed clear voltage‑ and concentration‑dependent ion current blockages, consistent with transient peptide interactions within the OmpF lumen. Peptide length influenced the characteristics of these interactions: longer protamine fragments produced weaker and less frequent blockages. At low transmembrane potentials, all peptides interacted weakly with the pore, whereas higher potentials increased the likelihood and duration of detectable events. These findings establish OmpF as a tractable system for probing cationic peptide–channel interactions and provide a descriptive framework for understanding how arginine‑rich peptides engage with β‑barrel pores due to likely electrostatic trapping, without implying specific transport pathways or translocation mechanisms.

Molecular Mechanisms and Therapeutic Targeting of the Macrophage Metabolic-Epigenetic Interaction Network in Chronic Obstructive Pulmonary Disease - Qi Liu; Weiying Liu (Cell Biochemistry and Biophysics, 2026)

Integrated Phytochemical, Computational and In Vitro Evaluation of the Oocysticidal Activity of Pleurotus ostreatus Extract Against Cryptosporidium parvum - Amal M. Marey; Mohamed A. Dkhil; Shaimaa M. Kasem; Seifeldin Elabed; Felwa A. Thagfan; Mohga S. Abdalla (Cell Biochemistry and Biophysics, 2026)